CHILD PASSENGER SAFETY - Haironi, Haironi; Jusmadi, Jusmadi; Masyduki, Masyduki; Jusnaidi, Jusnaidi; Helman, Mhd; Misran, Misran; Cuadmadja, Anera Irinsyahinta; Fikri, KMS. Novyar Satriawan (Yayasan Education and Social Center, 2025)
Child passenger safety has significantly progressed over the last decade, yet motor vehicle collisions remain the primary cause of mortality for children aged four and above. This policy statement presents four evidence-based suggestions for optimal practices in selecting a child restraint system to enhance safety in passenger vehicles for children from infancy to adolescence: (1) Utilize rear-facing car safety seats for as long as feasible; (2) Transition to forward-facing car safety seats once children surpass the limits of rear-facing seats, typically until at least 4 years of age; (3) Employ belt-positioning booster seats after outgrowing forward-facing seats, generally until at least 8 years of age; and (4) Implement lap and shoulder seat belts for all individuals who have exceeded the requirements for booster seats. Furthermore, a fifth evidence-based recommendation stipulates that all children under 13 should occupy the rear seats of cars. It is crucial to acknowledge that each change entails a reduction in protection, so parents should be motivated to postpone these transitions for the maximum duration. These suggestions are formulated as an algorithm designed to assist pediatricians in implementing them for their patients and families, addressing most scenarios encountered in practice. The American Academy of Pediatrics advocates that all physicians familiarize themselves with and endorse these suggestions as integral components of child passenger safety anticipatory guidance during each health supervision appointment